Identificação de um modelo constitutivo para simulação computacional do processo de prensagem a frio de um material refratário sílico-aluminoso - Montilha, Fernanda Silveira (Universidade Federal de São Carlos, 2016)
One of the methods for the processing of refractory material is cold pressing of the powder material, followed by sintering. Heterogeneous distribution of density can occur in the green compact during pressing because of the friction between the particles of the material and the pressing tools, that may hinder the sintering step. In this context, the simulation of the pressing process constitutes an important tool for the study and improvement of this step, to obtain green compacts with good microstructural homogeneity and also analyze the pressing tools to optimize its design in industrial applications. The identification of a constitutive model to represent the powder material is required to perform the simulation and it is the most complex step. The Drucker-Prager/Cap model implemented in the commercial software of finite elements, AbaqusTM, is suitable primarily for soil compaction study and is able to simulate the mechanical compaction of particulate materials. The parameters of this model have been obtained for a silico-aluminous refractory by a combination of simple, diametrical and hydrostatic compression tests. In studies available in the literature, the material models are partially identified, and in many cases, inadequate simplifications are applied. This study aimed to identify the parameters of the material model more precisely using the digital images correlation technique in the mechanical tests, which enabled a greater understanding of the yielding mechanisms and the achievement of data not obtained by conventional techniques. This methodology allowed the identification of a constitutive model and it was valitaded by the good agrrement between experimental results and those obtained in computer simulations, applied to a uniaxial case followed by isostatic pressing.
Keywords: Prensagem a frio; Compacto verde; Refratário; Drucker-prager cap; Elementos finitos; Cold Pressing; Green Compact; Refractory; Finite Elements; Digital Image Correlation; Dilatancy; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO